Synthesis Of Curcumin Loaded Chitosan Nanoparticles, Their Characterization And Anticancer Activity (Applied Biological Research, 2022)
This study was designed to encapsulate curcumin in chitosan nanoparticles  synthesized by ionic gelation method. In dissolution studies, curcumin was  found insoluble in water, slightly soluble in HCl, H2SO4 and phosphate  buffer saline (PBS) [pH 6.8, 8.4] but highly soluble in ethanol and dimethyl  sulfoxide. Fourier transform infrared spectroscopy (FTIR) analysis of pure  curcumin revealed the presence of different functional groups. In an  attempt to optimize the best suited nanoparticles, three different  formulations were prepared with increasing concentration of curcumin.  Curcumin (CRN) @ 500 mg kg-1 was found to be the best formulation with  particle size of 844 nm, zeta potential of -32.7 mV, encapsulation efficiency  of 70.9%, and loading efficiency of 9.2%. Further, it was characterized by  FTIR, X-ray diffraction spectroscopy (XRD), and scanning electron  microscopy (SEM) analysis. In vitro drug release studies showed the initial  burst release followed by slow and steady release up to 100 h. Finally, pure  CRN anticancer activity is compared with chitosan nanoparticles (CNPs)  loaded with CRN. Percentage of cells viable decreased with increase in the  concentration of both CRN and CRN-CNPs-1. CRN loaded in CNPs was  founmore effective than pure CRN. Thus, the study revealed the  successful encapsulation of curcumin and increasing therapeutic  in in the treatment of breast cancers.
Keywords: Breast cancer; ionic gelation method; FTIR; SEM; XRD; MCF-7 cells